PSIV-15 Examining the relationship between breed type and anabolic implant protocols in performance in the feedlot, health, and temperament of beef steers. (8th October 2021) - Reichhardt, Caleb C; Alberto, Anthony F; Briggs, Reganne K; Smith, Laura A; Okamoto, Lillian L; Roholt, Bryce; Bowman, Brett; Garcia, Matthew D; Thornton, Kara J
Abstract: The purpose of this research was to compare anabolic implant protocols in feedlot steers of two different breed types. Sixty steers were stratified by weight and breed in a 2 x 3 factorial design examining two different breeds: Angus (AN; n = 38) or Santa Gertrudis influenced (SG; n = 22), and three implant strategies: no implant (CON; n = 20), a moderate implant protocol (d0 implant: Revalor-G, d56 implant: Revalor-IS, d112 implant: Revalor-S; MOD; n = 20), or a vigorous implant protocol (d0 implant: Revalor-IS, d56 implant: Revalor-S, d112 implant: Revalor-200; VIG; n = 20). Steers were randomly placed into pens equipped with GrowSafe® bunks and fed the same ration. Weight, chute score (CS), exit velocity, blood, temperature, hip height and 12 th rib fat thickness were collected approximately every 28d over a 112d period. Over the 112 d, SG steers tended (P = 0.10) to gain more hip height than AN steers. Anabolic implant protocol influenced total gain with both VIG and MOD steers gaining more (P < 0.01) than CON. On d 0, SG steers had a higher (P < 0.01) CS compared to AN steers, with this being maintained through the course of the trial. There was also as a tendency for there to be a breed*treatment effect (P = 0.06) on d112, with SG-MOD having a higher (P = 0.04) CS than AN-VIG, and a tendency (P = 0.08) for SG-VIG to have a higher CS than AN-VIG. Moderate and VIG implant protocols may be a useful tool to increase performance in feedlot steers. However, this research did find that SG influenced steers may have a more excitable temperament, but implant protocol did not influence (P > 0.05) temperament.